Improved underwater laser cutting of thick steel plates through initial oblique cutting. (September 2021) - Shin, Jae Sung; Oh, Seong Y.; Park, Seung-Kyu; Park, Hyunmin; Lee, Jonghwan
Highlights: Underwater laser cutting tests of thick steel plates were conducted with the initial oblique cutting. Cut tests were performed both stainless and carbon steel plates for oblique angles of 5° and 15°. Compared to the straight cutting, the initial cutting speed was significantly increased. At the oblique angle of 15°, 2-step cutting with low initial cutting speed was no longer necessary. Abstract: In underwater laser cutting of steel plates thicker than 40 mm, the initial cutting speed was previously limited to 5–10 mm/min, because the generated melt could not be smoothly blown near the start point. Oblique cutting was considered a way to overcome this problem and speed up the initial cut. For this reason, underwater laser cutting tests were conducted to verify the improvement in initial cutting performance of thick steel plates through oblique cutting. First, constant speed cutting tests at oblique angle of 5° were performed on stainless steel plates. Compared to straight cutting, this method allowed initial cutting speed to be significantly increased. The maximum initial cutting speeds were 50, 25, and 15 mm/min for thicknesses of 48, 57, and 67 mm, respectively. When the oblique angle further increased to 15°, the initial cutting speed reached the maximum cutting speed achievable for each thickness. Therefore, there was no longer a need for 2-step cutting with low initial cutting speed. The maximum cutting speeds at the oblique angle of 15° were 100, 50, and 15 mm/min for thicknesses of 48, 57, and 68 mm, respectively. Additional cutting tests were performed for carbon steel plates. Due to the material properties of carbon steel, its cutting speed must be lower than that of stainless steel; however, all specimens were successfully cut at the oblique angle of 15°. The maximum cutting speeds of carbon steel plates were 40, 15, and 7 mm/min for thicknesses of 48, 59, and 69 mm, respectively.